PERAN E-GOVERNMENT DALAM MEMBANGKITKAN USAHA KECIL MENENGAH DI DAERAH ISTIMEWA YOGYAKARTA DI MASA PANDEMI COVID-19 - Sri Lestari Harjanta (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2022)
The economy has been one of the hardest hit sectors during the COVID-19 pandemic. This condition is also felt by the Micro, Small and Medium Enterprises (UMKM) group in the Special Region of Yogyakarta (DIY). In the Special Region of Yogyakarta (DIY), 59 percent of MSMEs experienced the direct impact of the Corona virus pandemic. Responding to this condition, the DIY Cooperatives and SMEs Service through the SiBakul Jogja (e-gov) program wants to help SMEs due to the impact of the pandemic. In SiBakul Jogja, for the Markethub service (marketplace) and also for the free shipping program. This research has two objectives. The first objective is to find out the role of E-Government in raising SMEs in DIY during the Covid-19 pandemic. And second, knowing the inhibiting factors for the implementation of SiBakul Jogja in improving the performance of MSEs in DIY. While the research method used is descriptive qualitative research method. The results of this study conclude, the role of E-Government through SiBakul Jogja which includes markethub services and free postage programs has helped SMEs. Through markethub, SMEs can market their products online. The free shipping program is also a magnet for shoppers selling or shopping through SiBakul Jogja. The free shipping budget which always increases every year shows that the program has received a positive response both for consumers and SMEs who are members of the SiBakul Jogja markethub.